2017
DOI: 10.1007/s10661-017-5784-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of spatial empirical models to estimate soil erosion in arid ecosystems

Abstract: The central objective of this project was to utilize geographical information systems and remote sensing to compare soil erosion models, including Modified Pacific South-west Inter Agency Committee (MPSIAC), Erosion Potential Method (EPM), and Revised Universal Soil Loss Equation (RUSLE), and to determine their applicability for arid regions such as Kuwait. The northern portion of Umm Nigga, containing both coastal and desert ecosystems, falls within the boundaries of the de-militarized zone (DMZ) adjacent to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…At the national and regional levels, soil erosion is regarded as one of the primary mechanisms of desertification processes. [1]. Soil erosion has been identified as one of the most serious natural problems worldwide due to the catastrophic environmental and economic consequences of the various stages of soil loss and sedimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the national and regional levels, soil erosion is regarded as one of the primary mechanisms of desertification processes. [1]. Soil erosion has been identified as one of the most serious natural problems worldwide due to the catastrophic environmental and economic consequences of the various stages of soil loss and sedimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Several empirical models are proposed to predict the soil erosion by water and 1090 (2022) 012004 IOP Publishing doi:10.1088/1755-1315/1090/1/012004 2 associated sediment yield. The problem with those models is that the most of them are not well tested and require several parameters, but they are used due to their simplicity [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies have been conducted to compare different models such as EPM, PSIAC, and MPSIAC to estimate the sedimentation yield (Mirakholro and Rahimzadegan, 2018;Zarei et al, 2019). Abdullah et al (2017) used MPISIAC, EMP, and RUSLE empirical models to investigate the amount of erosion in the Um-Niga region of Kuwait. The results showed that the RUSLE model did not have good accuracy, but the MPSIAC and EMP models had acceptable and close results.…”
Section: Introductionmentioning
confidence: 99%
“…This comes in response to more rapid and widespread land degradation caused by climate change and anthropogenic activities [ 1 , 2 , 3 ]. Vegetation plays an essential role in combating desertification, enhancing human wellbeing, and reducing greenhouse gases through carbon sequestration [ 3 , 4 , 5 ]. However, revegetation in dryland areas is an onerous task owing to a variety of interacting factors, including scarcity of water resources [ 6 ], unpredictable drought [ 7 , 8 ], salt-affected soil [ 9 ], limited acclimatization of species to harsh weather [ 10 ], human population growth, poor land mismanagement, and inadequate policies for ecosystem management [ 11 ].…”
Section: Introductionmentioning
confidence: 99%